Impact of PIEZO1‐channel on inflammation and osteoclastogenesis mediated via periodontal ligament fibroblasts during mechanical loading. (12th January 2023) - Schröder, Agnes; Neher, Katharina; Krenmayr, Bernhard; Paddenberg, Eva; Spanier, Gerrit; Proff, Peter; Kirschneck, Christian
Abstract: The identification of mechanosensitive ion channels and their importance in innate immunity provides new starting points to elucidate the molecular mechanisms of orthodontic tooth movement. The mechanosensitive electron channel PIEZO1 (Piezo Type Mechanosensitive Ion Channel Component 1) may play a crucial role in orthodontic tooth movement. To investigate the role of the PIEZO1 channel, periodontal ligament fibroblasts (PDLF) were subsequently treated with a PIEZO1 inhibitor (GsMTx) with simultaneous pressure application or with an activator (JEDI2) without mechanical strain. The expression of genes and proteins involved in orthodontic tooth movement was examined by RT‐qPCR, Western blot and ELISA. In addition, the effect on PDLF‐mediated osteoclastogenesis was investigated in a coculture model using human monocytes. Inhibition of PIEZO1 under pressure application caused a reduction in RANKL (receptor activator of NF‐kB ligand) expression, resulting in decreased osteoclastogenesis. On the other hand, activation of PIEZO1 without mechanical strain downregulated OPG (osteoprotegerin), resulting in increased osteoclastogenesis. PIEZO1 appears to play a role in the induction of inflammatory genes. It was also shown to influence osteoclastogenesis.